Drop-Set resistance training versus pyramidal and traditional sets elicits greater psychophysiological responses in men - Enes, A.; Oneda, G.; Leonel, D. F.; Ramos, R. A.; Kvas-Cabral, V. C.; Bernardo, M. F.; Escalante, G.; Souza-Junior, T. P. (Perceptual and Motor Skills, 2023)
We compared the effects of resistance training (ResisT) to pyramidal and traditional weightlifting sets on men`s psychophysiological responses. In a randomized crossover design, 24 resistance-trained males performed drop-set, descending pyramid, and traditional ResisT in the barbell back squat, 45° leg press, and seated knee extension. We assessed participants` rating of perceived exertion (RPE) and feelings of pleasure/displeasure (FPD) at the end of each set and at 10, 15, 20, and 30 minutes post-session. No differences were detected across ResisT Methods in total training volume (p = 0.180). Post hoc comparisons revealed that drop-set training elicited higher RPE (M 8.8 SD 0.7 arbitrary units) and lower FPD (M -1.4 SD 1.5 arbitrary units) values compared to descending pyramid (M Set RPE 8.0 SD 0.9 arbitrary units and M Set FPD 0.4 SD 1.6 arbitrary units) and traditional set (M Set RPE 7.5 SD 1.1 arbitrary units and M Set FPD 1.3 SD 1.2 arbitrary units) schemes (p < 0.05). In addition, drop-set training elicited higher session RPE (M 8.1 SD 0.8 arbitrary units) and lower session FPD (M 0.2 SD 1.4 arbitrary units) values than descending pyramid and traditional ResisT (p < 0.001). Similarly, descending pyramid training elicited higher session RPE (M 6.6 SD 0.9 arbitrary units) and lower session FPD (M 1.2 SD 1.4 arbitrary units) than traditional set (M Session RPE 5.9 SD 0.8 arbitrary units and M Session FPD 1.5 SD 1.2 arbitrary units) training (p = 0.015). No differences were found in the temporality of post-session metrics, suggesting that testing 10 and 15 minutes post-ResisT was sufficient to assess session RPE (p = 0.480) and session FPD (p = 0.855), respectively. In conclusion, even with similar total training volume, drop-set training elicited more pronounced psychophysiological responses than either pyramidal or traditional ResisT in resistance-trained males.